2019
DOI: 10.1016/j.omega.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

On the optimal marketing aggressiveness level of C2C sellers in social media: Evidence from china

Abstract: Social media has become a widely used marketing tool for reaching potential customers. Because of its low cost, social media marketing is especially appealing to customer-to-customer (C2C) sellers. Customers can also benefit from social media marketing by learning about products and by interacting with sellers in real time. However, a seller's marketing microblogs may backfire on her for dominating the social space. Defining the marketing popularity as the average number of likes each seller receives per marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Bigne et al (2019) aimed assessing the impact of destination marketing organization's Twitter activity on hotel occupancy rates through employing Artificial Neural Network (ANN) method, and managed to estimate hotel occupancy rate with above 90% accuracy by using the number of retweets and replies by users, the number of event tweets, tourist attraction tweets, and retweets. In order to quantify the optimal level of marketing aggressiveness in social media for reaching the maximum popularity, Wang et al (2019) employed Naïve Bayes method and more than 700.000 posts on Sina Weibo, and concluded that marketing aggressiveness can predict marketing popularity with 96% accuracy.…”
Section: Svm For Purchase Intention;mentioning
confidence: 99%
See 1 more Smart Citation
“…Bigne et al (2019) aimed assessing the impact of destination marketing organization's Twitter activity on hotel occupancy rates through employing Artificial Neural Network (ANN) method, and managed to estimate hotel occupancy rate with above 90% accuracy by using the number of retweets and replies by users, the number of event tweets, tourist attraction tweets, and retweets. In order to quantify the optimal level of marketing aggressiveness in social media for reaching the maximum popularity, Wang et al (2019) employed Naïve Bayes method and more than 700.000 posts on Sina Weibo, and concluded that marketing aggressiveness can predict marketing popularity with 96% accuracy.…”
Section: Svm For Purchase Intention;mentioning
confidence: 99%
“…D'avanzo ( 2017) conducted sentiment analysis with 3.000 tweets for presenting a pipeline that enables decision makers to monitor Twitter's sentiment on the topics of Google trends, and through employing four sentiment analysis tools (naїve Bayes detection algorithm, a simple voter algorithm, an NLTK-based sentiment analysis algorithm, commercial sentiment analysis tool) plausibility of their approach is validated. Four studies (Ghiassi et al, 2013;Ikeda et al, 2013;Pournarakis et al, 2017;Bigne et al, 2019) applied more complex machine learning methods for conducting research through employing consumer tweets, and Wang et al (2019) by employing messages posted on micro blog Sina Weibo. Ghiassi et al (2013) employed above a million consumer tweets for developing a sentiment classification using SVM, and by using that Twitter-specific lexicon and DAN2 machine learning approach, they found 181 terms of sentiment expressions and 6 brand specific ones with effective recall and accuracy metrics.…”
Section: Svm For Purchase Intention;mentioning
confidence: 99%
“…There are approximately 2.46 billion social media users globally [18]. Because of its extreme popularity and low cost solution, social media is now being utilised as a marketing tool, especially by customer-to-customer (C2C) ventures [19]. Introduction of Mobile Web 2.0, an evolution of Web 2.0 for mobile devices, the scope of social media and thus social commerce has expanded and migrated to mobile platform [18,20].…”
Section: Adoptionmentioning
confidence: 99%
“…The C2C mode mainly refers to that the network service providers supply the paid or unpaid e‐commerce platform to allow both parties (mainly individual users) to carry out an online transaction by bidding and bargaining 2 . In recent years, Chinese C2C market has been in a stage of rapid growth 3 . This mode has become an entrepreneurial method for many small capital holders.…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, Chinese C2C market has been in a stage of rapid growth. 3 This mode has become an entrepreneurial method for many small capital holders. However, due to the virtual nature of online transactions, buyers and sellers are usually in a non-face-to-face environment during the transaction process.…”
Section: Introductionmentioning
confidence: 99%